1998
DOI: 10.1029/98jb00390
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the ice‐sheet surface and subsurface topography above the Vostok Station subglacial lake, central East Antarctica

Abstract: Abstract. Radio-echo sounding (RES) and satellite radar-altimeter data were analyzed in order to identify the surface and subsurface topography around the largest known subglacial lake, at Vostok Station, East Antarctica (named here as Lake Vostok). In doing so, a data set was established from which a qualitative description of the flow of ice across the lake was developed. Patterns of ice flow were constructed through consideration of (1) the ice-sheet surface from the satellite altimeter and (2) internal lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
4
42
0
Order By: Relevance
“…The RES data show a distinct bending in the internal layering that can be modelled when zones of melting and freezing (in the order of several centimetres per year) are introduced. Internal layering features similar to those in Figure 2 occur across other parts of the western lake margin to the north of our flowline (Siegert and Ridley, 1998). If these RES features are also caused by zones of melting and freezing, then a continuous zone of basal melting may exist from our investigated flowline, northwards, along the western margin of the lake.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The RES data show a distinct bending in the internal layering that can be modelled when zones of melting and freezing (in the order of several centimetres per year) are introduced. Internal layering features similar to those in Figure 2 occur across other parts of the western lake margin to the north of our flowline (Siegert and Ridley, 1998). If these RES features are also caused by zones of melting and freezing, then a continuous zone of basal melting may exist from our investigated flowline, northwards, along the western margin of the lake.…”
Section: Discussionmentioning
confidence: 91%
“…The RES profile (Fig. 2a) shows clear internal reflections in the ice which are interpreted as isochrons (Smith, 1996;Siegert and Ridley, 1998).…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A subglacial lake the size of Lake Ontario would have significantly influenced the surface topography of the overlying ice sheet in a fashion similar to that documented from the Antarctica Ice Sheet (Siegert and Ridley, 1998). The largest documented subglacial lake beneath the Antarctic Ice Sheet is Lake Vostok and is overlain by ice with a surface topography of 0.004°slope (0.25 m km -1 ; Siegert 2000).…”
Section: The Confining Ice Lidmentioning
confidence: 99%
“…From airborne radar data, Siegert and Ridley [1998] demonstrated that the ice sheet first thins, then thickens, as the ice cross es the lake. These changes appear to be driv en by the melting and refreezing processes at the base of the ice sheet.…”
Section: Clearly Visible From Spacementioning
confidence: 99%